2016
DOI: 10.1007/s11547-016-0648-z
|View full text |Cite
|
Sign up to set email alerts
|

Resected pN1 non-small cell lung cancer: recurrence patterns and nodal risk factors may suggest selection criteria for post-operative radiotherapy

Abstract: Nodal factors as high LNR and ECE can predict an increased risk of worse FFLR and PFS. Prospective data on selected patients, treated with modern radiotherapy techniques, need to be collected to re-evaluate the role of radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated that LNR is a reliable predictor of survival and postoperative recurrence in resectable NSCLC patients with lymph node metastasis. [36][37][38][39] However, the cut-off values of LNR differed among these reports, ranging from 0.12 to 0.34. Our study is the first to specially demonstrate that LNR is an independent predictor of early recurrence in stage pIIIA-N2 NSCLC undergoing curative resection.…”
Section: Discussionmentioning
confidence: 90%
“…Several studies have demonstrated that LNR is a reliable predictor of survival and postoperative recurrence in resectable NSCLC patients with lymph node metastasis. [36][37][38][39] However, the cut-off values of LNR differed among these reports, ranging from 0.12 to 0.34. Our study is the first to specially demonstrate that LNR is an independent predictor of early recurrence in stage pIIIA-N2 NSCLC undergoing curative resection.…”
Section: Discussionmentioning
confidence: 90%